The Use of Educational Video in Increasing Tobacco Farmers’ Knowledge of First Aid Green Tobacco Sickness (GTS) - Novitasari, Fadilla Aulia Dwi; Hidayati, Nur; Kusbiantoro, Dadang (Babali Publisher, 2023)
Introduction: The tobacco production process has a negative health impact on tobacco workers. Every day, tobacco farmers who plant, process, and harvest can absorb as much nicotine as the amount of nicotine found in 50 cigarettes. Therefore, tobacco farmers are at risk of acute nicotine poisoning known as Green Tobacco Sickness (GTS). The aim of the study was to determine the effect of educational videos on increasing tobacco farmers’ knowledge of first aid for GTS in Kedungadem Village, Kedungadem District, Bojonegoro Regency. Method. This research used pre-experimental one group pre-test post-test design. The population was 129 tobacco farmers. The sample was 97 tobacco farmers who were recruited by cluster random sampling. The data were obtained by a questionnaire and analyzed by paired t-test (α≤0.05). Result. The results showed that 63 farmers (64.5%) had a low level of knowledge before educational videos were played and increased to 84.5% after the videos were played. The results of the paired t-test indicated that there was an effect of educational videos on tobacco farmers’ knowledge of first aid for GTS (P = 0.000). Conclusion. Health education using videos can increase tobacco farmers' knowledge about first aid for GTS. Videos can be used as alternative media for providing health education to the community. Further researchers can provide a control group and/or using a different method.